Novel Molecular Mechanisms of Gangliosides in the Nervous System Elucidated by Genetic Engineering - Furukawa, Koichi (Int J Mol Sci, 2020)
Acidic glycosphingolipids, i.e., gangliosides, are predominantly and consistently expressed in nervous tissues of vertebrates at high levels. Therefore, they are considered to be involved in the development and function of nervous systems. Recent studies involving genetic engineering of glycosyltransferase genes have revealed novel aspects of the roles of gangliosides in the regulation of nervous tissues. In this review, novel findings regarding ganglioside functions and their modes of action elucidated mainly by studies of gene knockout mice are summarized. In particular, the roles of gangliosides in the regulation of lipid rafts to maintain the integrity of nervous systems are reported with a focus on the roles in the regulation of neuro-inflammation and neurodegeneration via complement systems. In addition, recent advances in studies of congenital neurological disorders due to genetic mutations of ganglioside synthase genes and also in the techniques for the analysis of ganglioside functions are introduced.